Penguatan Pendidikan Karakter Peserta Didik Sesuai Enam Pilar Karakter Di Nadzom Alala di Era 5.0 - Syahir Naashiruddin; Subar Junanto (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
Character education is the main value that a learner must have, especially in facing global challenges and the rapid development of information technology. Therefore, it is necessary to strengthen the character of a learner who is relevant to what they experience. Here the basis of the strengthening literature is to use the 6 pillars of character value in a nadzom alala. This study uses the library research method by looking for papers that are relevant to the theme raised and then analyzed and described. The problem of Character Education in Era 5.0 is where Technology and Information can be enjoyed by all parties, not only adults but even small children can now enjoy it and there are also internal and external factors from the human The form of character education in Nadhom Alala is 6: Smart, earnest, patient, cost, teacher's blessing and long time.